Primary urothelial carcinoma of an ileal conduit; six decades after childhood bladder exstrophy surgery: a rare and late complication - Areeba Ahmed; Sameen Nasir; Imran Khan Jalbani; Amna Qadri (World Journal of Surgical Oncology)
Abstract Background Bladder exstrophy is a rare congenital anomaly that requires surgical reconstruction or urinary diversion early in life. While adenocarcinoma is the most commonly associated malignancy, primary urothelial carcinoma arising within an ileal conduit without any evidence of disease in the entire urinary tract is exceedingly rare and has never been reported before. Case presentation We report a case of a 64-year-old male with a history of bladder exstrophy managed with an ileal conduit in early childhood. He presented with intermittent bleeding from his urinary stoma, and subsequent evaluation revealed a high-grade invasive urothelial carcinoma arising within the ileal conduit, without involvement of the ureteric orifices or native urinary tract. Metastatic spread to the regional lymph nodes and liver underscored the aggressive disease course. Despite prompt initiation of chemotherapy and later immunotherapy, the disease progressed rapidly, leading to severe complications, including bilateral hydronephrosis requiring percutaneous nephrostomy. The patient was ultimately transitioned to palliative care. Conclusion Primary urothelial carcinoma in an ileal conduit of bladder exstrophy patient is a rare condition. The latency period for the onset of this aggressive cancer in urinary diversions can be long but mainly occurs before the age of 65. This reinforces the need for long-term follow-up of patients with urinary diversions, even in the absence of symptoms. We advocate for routine screening of these patients, initiating before the age of 30 as previously recommended for bladder exstrophy patients.